A new generalization of elliptic type integrals - Molina, Beatriz; Galué, Leda (Rev. Téc. Fac. Ing. Univ. Zulia)
The integrals of elliptic type appear in several problems of physical radiation: they have many applications in problems of illumination and heal exchange, in studies of civil defense to predict the radiation field produced by nuclear accidents and the irradiation technology in medicine, agriculture and industry. These integrals have been studied and generalized by several authors. In this paper we define a new generalization of elliptic type integrals. giving for this particular cases, recurrence relations, representations in series. differential recurrence relations and evaluation of some integrals.